Moralidade e eticidade: uma discussão entre Kant e Hegel - Araújo Neto, José Aldo Camurça de (2011)
The issue of morality can be studied through an apparently simple question: how I must act? This question, however, unchains a series of new questions: how can I judge my actions and other people’s actions? What are the criteria according to which I make this judgment? Which principles and values must guide my actions? What is the relation between individual morality and social normativity? Answering all these questions do not deplete the problem of morality, since each question may generate a multitude of others which, in their turn, demand more elaborated answers each time. Immanuel Kant and Georg Wilhelm Friedrich Hegel try, in their own way, to give a satisfactory reply to this polarization. In fact, the object of main analysis of morality is the individual, the citizen who acts in the world. It is in the world that societies create criteria and values, so that the actions of individuals can be recognized in the world. However, to be sure that their actions become valid, the individuals externalize their wills and inclinations in the institutions: family, civil society and the State. On these grounds, we find Kantian philosophy as opposite to Hegelian philosophy. On the one hand, we find a philosophy which excludes the sensitivity of human actions in order to claim the existence of a being that surpasses the empiricist, the sensitiveness: Kant and his Categorical Imperative. On the other hand, we find a philosophy which values the development of the idea of freedom in all its mediations – from the most abstract moment to the most concrete one – seeing this development as complete and systematic: the Hegelian philosophy. Between these two divergent viewpoints, there is morality. Whereas Kant conceives the content of moral action in an uninterested way, that is, the fulfillment of our actions only for the sake of our duty. The moral action in Hegel doesn’t happen without interest; we are motivated, therefore, by passion, inclinations, desires amongst other feelings. Despite all these differences, Kant and Hegel contribute a lot to the problematic of morality either in Ethics or in the realm of political philosophy. In Kant, the concept of autonomy makes the individual independent and capable of legislating in his/her own favor, controlling and guiding their act according to certain criteria and principles. In Hegel, freedom is internalized into morality, so that the individual assumes, conscientiously, the consequences of his/her own actions, being responsible for them. For this reason, the relation between the two philosophies is extremely fruitful and we cannot neglect one in detriment of the other. Hegel’s critique of Kantian moral philosophy is possible either in the realm of morality or in the realm of History because Kant himself gave the seeds to be criticized later. In other words, from the questionings about traditional metaphysics, the philosopher of Königsberg is a target for many different interpretations. Amongst these interpretations, Hegel is found with his notion of Ethicity.